Branding as innovation within agribusiness value chains. Issue 2 (14th October 2014) - Lewis, Gemma; Crispin, Stuart; Bonney, Laurie; Woods, Megan; Fei, Jiangang; Ayala, Sarah; Miles, Morgan
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to explore how traditional agribusiness firms can differentiate their product through innovation and branding at the value chain level, through the application of entrepreneurial marketing (EM). Traditionally, fresh vegetable products have been marketed as unbranded commodities. Design/methodology/approach – To address the research aim, this paper used a case study, which included semi-structured interviews with managers and personnel and unstructured observation of supply chain processes. Findings – The findings are based on a Tasmanian fresh broccoli value chain and suggest that EM could be effectively integrated at a multi-firm level. Clear communication, knowledge sharing, and trusting relationships are necessary to create a shared vision and a sustainable value chain. Research limitations/implications – An increasing number of firms in the agribusiness sector are looking for strategies that can enhance value for themselves and members of their chain. EM as a strategy can help an entire value chain achieve product differentiation and co-innovation, with flow on benefits to the consumer. Originality/value – There is limited research at the entrepreneurial and marketing interface that explores the application of EM at an inter-organizational level. This paper is one of the first to investigate EM in context of a supply chain management, using a value chain innovation framework.